Bach's solo violin works: A performer's guide - Schröder, Jaap 1925-2020 (New Haven Yale University Press, 2007)
Long admired for his interpretation of Bach's six Sonatas and Partitas for unaccompanied violin, Jaap Schröder, a leading international soloist, here provides a detailed but informal guide to their performance. Bach?s sublime solo violin works have long been central to the baroque music repertoire. No serious violinist can avoid studying them, and few concert artists can resist the temptation of performing them.This is a book for advanced students and performers. Using it is an experience akin to a master class conducted by a uniquely accomplished practitioner. The text is devoted almost entirely to practical matters?bowing, phrasing, ornamentation, tempi, and so on. Schröder strongly recommends the use of a baroque violin and, especially, baroque bow, but his interpretive insights and suggestions are equally applicable to modern violinists.